Efeitos do tabelamento e da liberação do preço do leite - Leitão e Silva, Josué (Revista Ceres, 2025)
The author studied the controlled and free milkprice for the Belo Horizonte milkshed and showed the consequences of both prices on supply and demand for in natura milk production.